Incorporating Paragraph Punch into EFL Writing Class - Nia Pujiawati (ELT in Focus, 2018)
The research was aimed at examining the effectiveness of Paragraph Punch in developing students’ writing paragraph fluency. Classroom action research was implemented to address the research questions. Relating to participants, it involved thirty students of English Department, University of Singaperbangsa Karawang, who had enrolled in Writing for General Communication and have experience in using software. The data from the students in Cycle 1 and 2 were analyzed using the theory of writing skills developed by Lyer and a theory of the standard organizational patterns of the paragraph proposed by Oshima and Hogue for evidence of how Paragraph Punch affected their skill in paragraph composition. The study indicated that the software effectively enhance the students’ writing ability both in the process and learning products. Thus, it is recommended for English Teacher to use Paragraph Punch as alternative way to improve the teaching quality.